Lead Letter from the Excavations of Area ‘O-Western’ at the Berezan Settlement in 2017 - Chistov, Dmitry; Pavlichenko, Natalia (Hyperboreus, 2019)
In 2017, during excavations of an ancient Greek settlement-site on the island of Berezan in the mouth of the Dnieper and Bug estuary, the expedition of the State Hermitage found a letter on a twice folded lead plate. This letter, on the plate  broken on left and right, contains eight lines scratched in boustrophedon style. It was discovered in the ﬁll of a household pit located ca 50 m from the place where, in 1982, a fragmentary lead letter also of the 2nd quarter of the 6th century BC was found. Both the archaeological context (e.g. Attic pottery and ‘proto-Thasian’ amphorae were absent in the pit) and the palaeographic peculiarities of the inscription allow us to date the ﬁnd under consideration to the 1st half or even the 2nd quarter of the 6th century BC. This is the early pit-dwelling period in the occupation of the Berezan settlement. Despite the poor state of preservation of the letter here published, it may be concluded that it probably belongs to letters of economic contents, in particular, to a correspondence between a merchant who conducted large-scale exporting operations on the Berezan and his counteragent.